Pengembangan Literasi Informasi Berbasis Modul untuk Siswa Madrasah Aliyah Negeri - Rory Ramayanti; Agung Iranda (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2023)
Literacy of information is mandatory to student, teacher and librarian. There are some isues of literacy in Indonesia, such as the gap of information among regions, hoax, and unreliable source of information. Besides, the shortage of facility in library, teacher and librarian with competency to support literacy of information for student. Therefore, this research develops literation module of information in state madrasah aliyah, and senior high school. The approach of research Using research and development by conducting re-difinition, design and development. Research is made by six steps module, namely to determine isues and purpose, information acsess strategy, management of information, information usage, create product, evaluation on literacy skills. Module was validated by experts, they are the lecturers of library science, and library practitioners. Analisys using Aiken V, the results of content analysis shows that each activity between 0,66 to 1, it shows validated module with high and highest grade.